2020
DOI: 10.1039/d0ra01173h
|View full text |Cite
|
Sign up to set email alerts
|

Raman profile alterations of irradiated human nasopharyngeal cancer cells detected with laser tweezer Raman spectroscopy

Abstract: Radiotherapy has been widely used for nasopharyngeal carcinoma (NPC) treatment, which causes DNA damage and alterations of macromolecules of cancer cells. However, the Raman profile alterations of irradiated NPC cells remain unclear. In the present study, we used laser tweezers Raman spectroscopy (LTRS) to monitor internal structural changes and chemical modifications in NPC cells after exposure at a clinical dose (2.3 Gy) to X-ray irradiation (IR) at a single-cell level. Two types of NPC cell lines, CNE2(EBV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…future CTC and LM cells). Unlike most of the previous studies where the classification of spectra is done at a bulk level [23,62,63], the leave-one-cell-out analysis allowed us to demonstrate not only the ability to identify metastatic potential at a single-cell level but also the robustness of such classification by completely excluding representation of the test data from the training dataset.…”
Section: Resultsmentioning
confidence: 99%
“…future CTC and LM cells). Unlike most of the previous studies where the classification of spectra is done at a bulk level [23,62,63], the leave-one-cell-out analysis allowed us to demonstrate not only the ability to identify metastatic potential at a single-cell level but also the robustness of such classification by completely excluding representation of the test data from the training dataset.…”
Section: Resultsmentioning
confidence: 99%
“…A peak at 561 cm −1 was attributed to O-P-O bending mode v4 [42]. Vibrations at 752 cm −1 and 780 cm −1 were assigned to the DNA and uracil-based ring breathing mode, respectively [43,44]. ese bonds represent the cell nuclei and the intensity was the same in both intact disc and cell-loaded scaffolds.…”
Section: Confocal Raman Spectroscopymentioning
confidence: 93%
“…Roman et al reported a change in the lipid composition and concentration in prostate cancer cells after X-ray radiation [ 80 ]. Similarly, metabolic alterations of cancer cells after radiation were also seen in nasopharyngeal cancer [ 79 ], non-small lung cancer [ 83 ], and glioblastoma [ 82 ]. A study by Milligan et al found different biochemical responses between radio-resistant and radio-sensitive cell types in lung (H460), breast (MCF7), and prostate (LNCaP) cells [ 81 ].…”
Section: Raman Spectroscopy As a Label-free Tool For Cancer Metabomentioning
confidence: 99%
“…Besides chemotherapy, radiotherapy is the mainstay of the treatment for a range of types of cancer. Monitoring radiation-induced cellular response of cancer at both cell and tissue levels was studied by Raman spectroscopy [79][80][81][82][83]. Roman et al reported a change in the lipid composition and concentration in prostate cancer cells after X-ray radiation [80].…”
Section: Cellular Responses To Anti-cancer Drugs and Radiotherapymentioning
confidence: 99%